Consumer xenocentrism: applying Item Response Theory for in-depth measurement analysis - Sorge, Giovanna Domenici (2024)
This study examines the psychometric characteristics of four consumer xenocentrism (C-XEN) scales: C-XENO, C-XENSCALE, X-SCALE, and XEN-SCALE, applying Item Response Theory (IRT) methodologies to compare and assess these scales. The main goal is to determine how IRT might offer further understanding into the efficacy and precision of these scales. The investigation uncovers substantial similarities and repetitions in the measures, indicating possible areas for improvement. The results suggest that although each scale accurately assesses consumer xenocentrism, improvements in item clarity, reduction of redundancy, and overall scale optimization may significantly improve their reliability and suitability for use in various cultural settings.